Factors associated with knowledge and attitude related to oral health among older people living in the community, Malaysia - Syed Elias, Sharifah Munirah; Abdul Murad, Nur Amirah Syafiqah; Makhtar, Aniawanis; Pairoh, Hasanah (Tarbiat Modares University, 2024)
Aims: The prevalence of comorbidities among older individuals often leads to the neglect of oral health in this population. Therefore, this study aims to investigate the relationship between socio-demographic factors, knowledge, and attitudes related to oral health among older individuals. Instrument & Methods: A cross-sectional study was conducted, involving 359 individuals aged 60 and above in the community setting of Kuantan, Pahang, Malaysia. Data collection was carried out using a questionnaire distributed through social media platforms. The questionnaire comprised four sections: socio-demographics, self-perceived oral health status, knowledge, and attitudes. Data analysis was performed using SPSS 26. Findings: The mean total knowledge score was moderately good (17.42±5.74), and the mean total attitude score was positive (36.20±6.06). Educational level (p=0.01) and frequency of dental visits (p=0.02) were significantly associated with knowledge. Similarly, marital status (p=0.01), educational level (p=0.001), and frequency of dental visits (p=0.01) showed significant associations with attitude. We also identified a positive correlation between knowledge and attitudes related to oral health among older individuals (r=0.38, p=0.001). Conclusion: Among older individuals living in the community, knowledge of oral health was moderately good, and attitudes toward oral health were positive. Future oral health promotion efforts should specifically target individuals who are divorced or widowed, have lower educational levels, and have not visited dental clinics.